Volatile compounds and sensorial traits of "Toscano" dry-cured ham - Sirtori F.; Calamai L.; Giorgi W.; Tardelli L.; Pugliese C. (7th International Symposium on the Mediterranean Pig, 2012)
The aims of this study were to evaluate the effect of seasoning time on aromatic profiles and to describe the sensorial profile of “Toscano” dry-cured ham. At this aim ten hams, cured according to the rule of “Toscano” PDO label, were sampled at the begin of seasoning and at 1, 3, 6 and 12 months. The samples of muscular tissue were submitted to volatile compounds analysis by SPME-GC/MS. At the end of seasoning a sensorial analysis of hams was carried out by a trained panellist group. As regard volatile analysis, about 80 compounds were identified belonging to: aldehydes, organic acids, ketones, esters, alcohols and furans. Aldehydes represent the most important chemical family in “Toscano” ham; they showed a significant increase only in the first 6 months of seasoning. The second quantitatively important chemical family in “Toscano” ham was that of the organic acids that increased along the whole curing time. Ketones dramatically decreased at 12 months of seasoning while esters showed a more constant trend. Significant correlations were found among sensorial traits and aldehydes compounds.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)